Method for preparing and characterizing aluminum-rich supplementary gel and analyzing influence of aluminum-rich supplementary gel on cement

By preparing aluminum-rich supplementary cement without lithium ions and combining various analytical methods, the problem of lithium ions affecting pH was solved, the effective role of aluminum ions in cement was realized, the early strength and pore structure of cement were improved, and the mechanism of its influence on cement performance was revealed.

CN120847151APending Publication Date: 2025-10-28NANTONG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510997146.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-18
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing technologies often introduce lithium ions as catalysts when preparing aluminum-rich supplementary cementitious materials, which affects the pH and flowability of cement paste, and neglect the study of the differences between CASH and CSH and their impact on the hydration kinetics of cement-based materials.

Method used

A lithium-ion-free preparation method was adopted, and the aluminum-rich supplementary cementitious material was systematically characterized by X-ray diffraction, thermogravimetric analysis, Fourier transform infrared spectroscopy, and electron microscopy. The optimal preparation conditions were determined, and its impact on cement performance was analyzed.

Benefits of technology

This study ensures the effective function of aluminum ions in cement, avoids pH imbalance, refines pore structure, shortens setting time, improves early strength, and reveals the mechanism by which CASH affects cement performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120847151A_ABST
    Figure CN120847151A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing and representing aluminum-rich supplementary gel and analyzing influence on cement. The method comprises the following steps: step A, preparing multiple groups of cement supplementary gel prepared under different preparation conditions at the same time; step B, dividing the prepared multiple groups of different cement supplement gels into three groups of contrast test groups according to variables such as the raw materials with different molar ratios, different curing time and different curing temperatures; c, sequentially performing an X-ray diffraction experiment, a thermogravimetric analysis experiment, a Fourier transform infrared spectrum experiment, an electron microscope scanning experiment and the like on each control experiment group; parameters such as phase composition, thermal stability, bonding state, microstructure and particle size of the cement supplement gel generated under different preparation conditions are analyzed, and the optimal preparation condition of the cement supplement gel is selected; a systematic characterization analysis method is established to determine the structural characteristics of the cement, and the influence of the cement on the performance of the cement is explored.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials technology, specifically a method for preparing, characterizing, and analyzing the effects of aluminum-rich supplementary cementitious materials on cement. Background Technology

[0002] In recent years, researchers have focused on improving the early strength of cement-based materials to meet the demands of modern construction technologies. Nanoparticles, due to their high specific surface area, can accelerate cement hydration by speeding up the nucleation and growth process of CSH gels in the first few hours of the hydration reaction. With a deeper understanding of CSH gels, researchers believe that Al… 3+ It can be easily inserted into the structure of CSH gel, replacing the Si in the bridging silicon tetrahedron. 4+ The cement hydrates and enters the interlayer to balance the charge difference. In particular, when aluminum-rich supplementary cementitious materials are added to cement, the hydration product of cement is not CSH but CASH. In order to accelerate the crystallization efficiency of CASH and the early strength of cement-based materials, existing technologies often introduce lithium ions as a catalyst for hydrothermal synthesis. However, the addition of lithium ions will affect the pH required for the formation of supplementary cementitious materials and reduce the fluidity of cement paste. Moreover, these studies often only focus on the batching analysis of supplementary gels, thus neglecting the characterization analysis of supplementary gels. The research on the differences between CASH and CSH and their influence on the hydration kinetics of cement-based materials is also incomplete. Summary of the Invention

[0003] Purpose of the invention: In order to overcome the shortcomings of the existing technology, the present invention provides a method for the preparation, characterization and analysis of the effect of aluminum-rich supplementary cementitious material on cement, formulates a method for preparing cement supplementary gel without the addition of lithium ions to ensure that only aluminum ions have an effect, establishes a systematic characterization and analysis method to clarify its structural characteristics, and explores its effect on cement performance.

[0004] Technical Solution: To achieve the above objectives, the present invention provides a method for preparing, characterizing, and analyzing the impact of aluminum-rich supplementary cementitious materials on cement, comprising the following steps:

[0005] Step A: Simultaneously prepare multiple sets of cement supplement gels prepared under different conditions;

[0006] Step B: Based on variables such as different molar ratios of raw materials, different curing times, and different curing temperatures, the prepared multiple groups of different cement supplementary gels were divided into three control test groups;

[0007] Step C: Perform X-ray diffraction experiments on each control experimental group in sequence to analyze the phase composition of the cement supplement gel generated under different preparation conditions;

[0008] Step D: Perform thermogravimetric analysis on each control experimental group sequentially to analyze the thermal stability of the cement supplement gel generated under different preparation conditions.

[0009] Step E: Perform Fourier transform infrared spectroscopy experiments on each control experimental group in sequence to analyze the bonding state of the cement supplement gel generated under different preparation conditions;

[0010] Step F: Perform electron microscopy scanning experiments on each control experimental group in sequence to analyze the microstructure and particle size of the cement supplement gel generated under different preparation conditions;

[0011] Step G: Analyze the experimental results of steps C to F and select the optimal preparation conditions for cement supplement gel.

[0012] Furthermore, step A includes the following steps:

[0013] Step 1: Boil the deionized water and then cool it to 25°C to remove dissolved CO2, then transfer it to a polytetrafluoroethylene container;

[0014] Step 2: Add Ca(OH)2 to the deionized water from Step 1 and ultrasonically disperse it at a frequency of 20 kHz for at least 3 minutes;

[0015] Step 3: Based on Step 2, add nano-SiO2 to the deionized water and ultrasonically disperse it at a frequency of 20KHz for at least 3 minutes;

[0016] Step 4: Based on Step 3, add nano-Al2O3 to the deionized water and ultrasonically disperse it at a frequency of 20KHz for at least 3 minutes;

[0017] Step 5: Based on Step 4, seal the PTFE container and magnetically stir it at 95°C for 1.5 hours;

[0018] Step Six: After completing Step Five, transfer the sealed PTFE container to a water bath for curing.

[0019] Step 7: After completing Step 6, filter the polytetrafluoroethylene container synthesis product and transfer the filtered product to a washing device.

[0020] Step 8: Wash the synthesized product filtered in Step 6 with deionized water at least twice;

[0021] Step Nine: After completing Step Eight, wash the synthesized product filtered in Step Six with anhydrous ethanol at least twice.

[0022] Step 10: Place the synthetic product washed in Step 9 into a freeze dryer and dry it to constant weight to obtain C-(A)-SH.

[0023] Furthermore, in steps one to four, the molar ratio of the raw materials satisfies: Ca / Si = 0.5 to 1.5; Al / Si = 0 or 0.1; and the mass ratio of deionized water to the total mass of the raw materials is 8.0:1.

[0024] Furthermore, if Al / Si = 0, the synthetic product obtained in step six is ​​a cement supplement gel of the CSH phase; if Al / Si = 0.1, the synthetic product obtained in step six is ​​a cement supplement gel of the CASH phase.

[0025] Furthermore, in step five, the environment for water bath curing is a sealed container to prevent CO2 from entering.

[0026] Furthermore, in step six, the water bath temperature is 25℃~95℃, and the curing time is 1~7 days;

[0027] Furthermore, an analytical method for supplementing the effect of cementitious gel on cement includes the following steps:

[0028] Step S1: Prepare several identical portions of cement paste;

[0029] Step S2: Prepare several cement supplement gels according to the preparation method of cement supplement gel selected in step G;

[0030] Step S3: Add the cement supplement gel prepared in step S2 to the cement paste prepared in step S1 according to different dosages;

[0031] Step S4: Group the cement slurry with the same cement supplement gel into one group, and each part of cement slurry in each group is cured for a different duration.

[0032] Step S5: In step S4, the cement paste of each component is tested, and the effects of different dosages of cement supplementary gel on the workability, hydration heat release, pore structure and mechanical strength of cement-based materials at different curing times are analyzed.

[0033] Beneficial Effects: Compared with existing technologies, the method for preparing, characterizing, and analyzing the impact of aluminum-rich supplementary cementitious material of this invention does not require the introduction of harmful ions such as lithium ions, thus avoiding problems such as pH imbalance and reduced cement paste fluidity. Systematic characterization clarified the structural differences between CASH and CSH and the influence of preparation conditions, such as Al... 3+ It can improve density, and low-temperature curing is conducive to the formation of an ordered structure. At the same time, it reveals the mechanism of its influence on cement performance. CASH can refine the pore structure, shorten the setting time, improve the early strength, and the preparation process is stable. Attached Figure Description

[0034] Figure 1 To supplement the preparation flow chart of gel;

[0035] Figure 2 (a) XRD patterns of samples with different Ca / Si ratios cured at 95℃ for 7 days;

[0036] Figure 2 (b) shows the trend of the FWHM diffraction peak at 2θ = 29.22° as a function of Ca / Si;

[0037] Figure 3 (a) XRD patterns of samples with Ca / Si = 1.0 cured at 95℃ for different ages;

[0038] Figure 3 (b) shows the trend of the FWHM diffraction peak at 2θ = 29.22° with the curing time;

[0039] Figure 4 (a) XRD patterns of samples with Ca / Si = 1.0 cured at different temperatures for 7 days;

[0040] Figure 4 (b) shows the trend of the FWHM diffraction peak at 2θ = 29.22° with curing temperature;

[0041] Figure 5 TG spectra of samples with different Ca / Si ratios cured at 95℃ for 7 days;

[0042] Figure 6 TG-DSC spectra of samples with different Ca / Si ratios cured at 95℃ for 7 days;

[0043] Figure 7 TG spectra of samples with Ca / Si = 1.0 cured at 95℃ for different ages;

[0044] Figure 8 TG-DSC spectra of samples with Ca / Si = 1.0 cured at 95℃ for different ages;

[0045] Figure 9 TG spectra of samples with Ca / Si = 1.0 cured at different temperatures for 7 days;

[0046] Figure 10 TG-DSC spectra of samples with Ca / Si = 1.0 cured at different temperatures for 7 days;

[0047] Figure 11 FT-IR spectra of samples with different Ca / Si ratios cured at 95℃ for 7 days;

[0048] Figure 12 FT-IR spectra of samples with Ca / Si = 1.0 cured at 95℃ for different ages;

[0049] Figure 13 FT-IR spectra of samples with Ca / Si = 1.0 cured at different temperatures for 7 days;

[0050] Figure 14 SEM images of C-(A)-SH with different Ca / Si ratios cured at 95℃ for 7 days;

[0051] Figure 15 SEM images of C-(A)-SH with Ca / Si = 1.0 cured at 95℃ for different ages;

[0052] Figure 16 SEM images of C-(A)-SH with Ca / Si = 1.0 cured at different temperatures for 7 days;

[0053] Figure 17 The effect of different CASH dosages on the fluidity of cement paste;

[0054] Figure 18 The effect of different CASH admixtures on the setting time of cement paste;

[0055] Figure 19 (a) The effect of different CASH dosages on the hydration heat release rate of cement hydration behavior;

[0056] Figure 19 (b) The effect of different CASH dosages on the heat of hydration of cement hydration behavior;

[0057] Figure 20 The effect of different CASH dosages on the differential distribution curves of cement pore structure and pore size;

[0058] Figure 21 Pore ​​volume distribution of hardened cement paste

[0059] Figure 22 The effect of different CASH admixtures on the strength of cement mortar. Detailed Implementation

[0060] The invention will now be further described with reference to the accompanying drawings.

[0061] like Figure 1 As shown in Table 1, fourteen different experimental groups were established according to the data. Each experimental group is an example. The structural characterization of aluminum-containing supplementary gel was analyzed by comparing the examples of each group.

[0062]

[0063] Table 1 C-(A)-SH Raw material ratio and curing conditions

[0064] To facilitate understanding of the subsequent scheme, the different meanings in the name are explained here. Taking "CASH-0.5_95℃_7d" as an example, C represents Ca(OH)2; S represents nano SiO2; A represents nano Al2O3; H represents water, which is deionized water in this scheme; -0.5 represents the molar ratio of Ca(OH)2 to nano SiO2 is 0.5; _95℃ represents the curing temperature is 95℃; _7d represents the curing time is 7 days. It should be emphasized here that the molar ratio of nano Al2O3 to nano SiO2 is fixed at 0.1. Therefore, as long as nano Al2O3 is present in the raw materials for preparing cement supplementary gel, the molar ratio of nano Al2O3 to nano SiO2 will always be 0.1.

[0065] Example ①: Preparation of CSH-0.5 at 95℃ for 7 days

[0066] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2 and nano-SiO2 according to the molar ratio of Ca(OH)2 to nano-SiO2 of 0.5:1. The mass ratio of deionized water to the total mass of Ca(OH)2 and nano-SiO2 is 8.0:1.

[0067] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a polytetrafluoroethylene (PTFE) container. Weighed Ca(OH)2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Based on this, weighed nano-SiO2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Since the molar ratio of Al2O3 to SiO2 in this embodiment is 0, nano-Al2O3 was not added. The PTFE container was sealed and magnetically stirred at 95°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a 95°C water bath for curing for 7 days. The synthesized product in the PTFE container after curing was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The ethanol-washed synthesized product was placed in a freeze-drying oven and dried to constant weight to obtain CSH.

[0068] Example 2: Preparation of CASH-0.5_95℃_7d

[0069] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2, nano-SiO2, and nano-Al2O3 according to the molar ratio of Ca(OH)2 to nano-SiO2 of 0.5:1 and the molar ratio of Al2O3 to SiO2 of 0.1:1. The mass ratio of deionized water to the total mass of Ca(OH)2, nano-SiO2, and nano-Al2O3 is 8.0:1.

[0070] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a PTFE container. A weighed amount of Ca(OH)₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Next, a weighed amount of nano-SiO₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Finally, a weighed amount of nano-Al₂O₃ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. The PTFE container was then sealed. The mixture was magnetically stirred at 95°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a water bath at 95°C for 7 days of curing. The synthesized product in the PTFE container after curing was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The synthesized product washed with ethanol was placed in a freeze dryer and dried to constant weight to obtain CASH.

[0071] Example ③: Preparation of CSH-1.0 at 95℃ for 7 days

[0072] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2 and nano SiO2 according to the molar ratio of Ca(OH)2 to nano SiO2 of 1.0:1. The mass ratio of deionized water to the total mass of Ca(OH)2 and nano SiO2 is 8.0:1.

[0073] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a polytetrafluoroethylene (PTFE) container. Weighed Ca(OH)2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Based on this, weighed nano-SiO2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Since the molar ratio of Al2O3 to SiO2 in this embodiment is 0, nano-Al2O3 was not added. The PTFE container was sealed and magnetically stirred at 95°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a 95°C water bath for curing for 7 days. The synthesized product in the PTFE container after curing was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The ethanol-washed synthesized product was placed in a freeze-drying oven and dried to constant weight to obtain CSH.

[0074] Example 4: Preparation of CASH-1.0 at 95℃ for 7 days

[0075] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2, nano-SiO2, and nano-Al2O3 according to the molar ratio of Ca(OH)2 to nano-SiO2 of 1.0:1 and the molar ratio of Al2O3 to SiO2 of 0.1:1. The mass ratio of deionized water to the total mass of Ca(OH)2, nano-SiO2, and nano-Al2O3 is 8.0:1.

[0076] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a PTFE container. A weighed amount of Ca(OH)₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Next, a weighed amount of nano-SiO₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Finally, a weighed amount of nano-Al₂O₃ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. The PTFE container was then sealed. The mixture was magnetically stirred at 95°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a water bath at 95°C for 7 days of curing. The synthesized product in the PTFE container after curing was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The synthesized product washed with ethanol was placed in a freeze dryer and dried to constant weight to obtain CASH.

[0077] Example 5: Preparation of CSH-1.5 at 95℃ for 7 days

[0078] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2 and nano SiO2 according to the molar ratio of Ca(OH)2 to nano SiO2 of 1.5:1. The mass ratio of deionized water to the total mass of Ca(OH)2 and nano SiO2 is 8.0:1.

[0079] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a polytetrafluoroethylene (PTFE) container. Weighed Ca(OH)2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Based on this, weighed nano-SiO2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Since the molar ratio of Al2O3 to SiO2 in this embodiment is 0, nano-Al2O3 was not added. The PTFE container was sealed and magnetically stirred at 95°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a 95°C water bath for curing for 7 days. The synthesized product in the PTFE container after curing was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The ethanol-washed synthesized product was placed in a freeze-drying oven and dried to constant weight to obtain CSH.

[0080] Example 6: Preparation of CASH-1.5 at 95℃ for 7 days

[0081] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2, nano-SiO2, and nano-Al2O3 according to the molar ratio of Ca(OH)2 to nano-SiO2 of 1.5:1 and the molar ratio of Al2O3 to SiO2 of 0.1:1. The mass ratio of deionized water to the total mass of Ca(OH)2, nano-SiO2, and nano-Al2O3 is 8.0:1.

[0082] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a PTFE container. A weighed amount of Ca(OH)₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Next, a weighed amount of nano-SiO₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Finally, a weighed amount of nano-Al₂O₃ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. The PTFE container was then sealed. The mixture was magnetically stirred at 95°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a water bath at 95°C for 7 days of curing. The synthesized product in the PTFE container after curing was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The synthesized product washed with ethanol was placed in a freeze dryer and dried to constant weight to obtain CASH.

[0083] Example 7: Preparation of CSH-1.0 at 95℃ for 1 day

[0084] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2 and nano SiO2 according to the molar ratio of Ca(OH)2 to nano SiO2 of 1.0:1. The mass ratio of deionized water to the total mass of Ca(OH)2 and nano SiO2 is 8.0:1.

[0085] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a polytetrafluoroethylene (PTFE) container. Weighed Ca(OH)2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Based on this, weighed nano-SiO2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Since the molar ratio of Al2O3 to SiO2 in this embodiment is 0, nano-Al2O3 was not added. The PTFE container was sealed and magnetically stirred at 95°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a 95°C water bath for curing for 1 day. The synthesized product in the cured PTFE container was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The ethanol-washed synthesized product was placed in a freeze-drying oven and dried to constant weight to obtain CSH.

[0086] Example ⑧: Preparation of CASH-1.0 at 95℃ for 1 day

[0087] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2, nano-SiO2, and nano-Al2O3 according to the molar ratio of Ca(OH)2 to nano-SiO2 of 1.0:1 and the molar ratio of Al2O3 to SiO2 of 0.1:1. The mass ratio of deionized water to the total mass of Ca(OH)2, nano-SiO2, and nano-Al2O3 is 8.0:1.

[0088] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a PTFE container. A weighed amount of Ca(OH)₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Next, a weighed amount of nano-SiO₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Finally, a weighed amount of nano-Al₂O₃ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. The PTFE container was then sealed. The mixture was magnetically stirred at 95°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a water bath at 95°C for curing for 1 day. The synthesized product in the PTFE container after curing was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The synthesized product washed with ethanol was placed in a freeze dryer and dried to constant weight to obtain CASH.

[0089] Example 9: Preparation of CSH-1.0 at 95℃ for 3 days

[0090] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2 and nano SiO2 according to the molar ratio of Ca(OH)2 to nano SiO2 of 1.0:1. The mass ratio of deionized water to the total mass of Ca(OH)2 and nano SiO2 is 8.0:1.

[0091] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a polytetrafluoroethylene (PTFE) container. Weighed Ca(OH)2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Based on this, weighed nano-SiO2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Since the molar ratio of Al2O3 to SiO2 in this embodiment is 0, nano-Al2O3 was not added. The PTFE container was sealed and magnetically stirred at 95°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a 95°C water bath for curing for 3 days. The synthesized product in the cured PTFE container was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The ethanol-washed synthesized product was placed in a freeze-drying oven and dried to constant weight to obtain CSH.

[0092] Example 10: Preparation of CASH-1.0 at 95℃ for 3 days

[0093] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2, nano-SiO2, and nano-Al2O3 according to the molar ratio of Ca(OH)2 to nano-SiO2 of 1.0:1 and the molar ratio of Al2O3 to SiO2 of 0.1:1. The mass ratio of deionized water to the total mass of Ca(OH)2, nano-SiO2, and nano-Al2O3 is 8.0:1.

[0094] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a PTFE container. A weighed amount of Ca(OH)₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Next, a weighed amount of nano-SiO₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Finally, a weighed amount of nano-Al₂O₃ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. The PTFE container was then sealed. The mixture was magnetically stirred at 95°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a water bath at 95°C for 3 days of curing. The synthesized product in the PTFE container after curing was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The synthesized product washed with ethanol was placed in a freeze dryer and dried to constant weight to obtain CASH.

[0095] Example Preparation of CSH-1.0 at 25℃ for 7 days

[0096] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2 and nano SiO2 according to the molar ratio of Ca(OH)2 to nano SiO2 of 1.0:1. The mass ratio of deionized water to the total mass of Ca(OH)2 and nano SiO2 is 8.0:1.

[0097] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a polytetrafluoroethylene (PTFE) container. Weighed Ca(OH)2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Based on this, weighed nano-SiO2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Since the molar ratio of Al2O3 to SiO2 in this embodiment is 0, nano-Al2O3 was not added. The PTFE container was sealed and magnetically stirred at 25°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a water bath at 25°C for 7 days of curing. The synthesized product in the PTFE container after curing was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The ethanol-washed synthesized product was placed in a freeze dryer and dried to constant weight to obtain CSH.

[0098] Example Preparation of CASH-1.0_25℃_7d

[0099] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2, nano-SiO2, and nano-Al2O3 according to the molar ratio of Ca(OH)2 to nano-SiO2 of 1.0:1 and the molar ratio of Al2O3 to SiO2 of 0.1:1. The mass ratio of deionized water to the total mass of Ca(OH)2, nano-SiO2, and nano-Al2O3 is 8.0:1.

[0100] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a PTFE container. A weighed amount of Ca(OH)₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Next, a weighed amount of nano-SiO₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Finally, a weighed amount of nano-Al₂O₃ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. The PTFE container was then sealed. The mixture was magnetically stirred at 25°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a water bath at 25°C for 7 days of curing. The synthesized product in the PTFE container after curing was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The synthesized product washed with ethanol was placed in a freeze dryer and dried to constant weight to obtain CASH.

[0101] Example Preparation of CSH-1.0 at 60℃ for 7 days

[0102] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2 and nano SiO2 according to the molar ratio of Ca(OH)2 to nano SiO2 of 1.0:1. The mass ratio of deionized water to the total mass of Ca(OH)2 and nano SiO2 is 8.0:1.

[0103] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a polytetrafluoroethylene (PTFE) container. Weighed Ca(OH)2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Based on this, weighed nano-SiO2 was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Since the molar ratio of Al2O3 to SiO2 in this embodiment is 0, nano-Al2O3 was not added. The PTFE container was sealed and magnetically stirred at 60°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a 60°C water bath for curing for 7 days. The synthesized product in the cured PTFE container was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The ethanol-washed synthesized product was placed in a freeze-drying oven and dried to constant weight to obtain CSH.

[0104] Example Preparation of CASH-1.0_60℃_7d

[0105] Prepare raw materials: Weigh out the corresponding masses of Ca(OH)2, nano-SiO2, and nano-Al2O3 according to the molar ratio of Ca(OH)2 to nano-SiO2 of 1.0:1 and the molar ratio of Al2O3 to SiO2 of 0.1:1. The mass ratio of deionized water to the total mass of Ca(OH)2, nano-SiO2, and nano-Al2O3 is 8.0:1.

[0106] Deionized water was boiled and cooled to 25°C to remove dissolved CO2, then transferred to a PTFE container. A weighed amount of Ca(OH)₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Next, a weighed amount of nano-SiO₂ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. Finally, a weighed amount of nano-Al₂O₃ was added to the deionized water and ultrasonically dispersed at 20 kHz for at least 3 minutes. The PTFE container was then sealed. The mixture was magnetically stirred at 60°C for 1.5 hours. After magnetic stirring, the sealed PTFE container was transferred to a water bath at 60°C for 7 days of curing. The synthesized product in the PTFE container after curing was filtered, and the filtered product was transferred to a washing device. The filtered synthesized product was washed with deionized water at least twice. After washing with deionized water, the filtered synthesized product was washed with anhydrous ethanol at least twice. The synthesized product washed with ethanol was placed in a freeze dryer and dried to constant weight to obtain CASH.

[0107] The phase composition of the supplementary gel in each embodiment was analyzed by X-ray diffraction experiments.

[0108] X-ray diffraction experiments were performed on the samples generated in Examples ① to ⑥ to investigate the effect of different molar ratios of Ca(OH)2 and nano-SiO2 on the composition of the supplementary cementitious phase, and the results were as follows. Figure 2 (a) shows the XRD pattern; by detecting the diffraction signal generated by X-rays passing through the crystal, information such as the phase composition, crystal structure, grain size, and stress state of the material is analyzed; the analysis shows that when the molar ratio of Ca(OH)2 to nano-SiO2 in the synthesis raw materials is 0.5 and 1.0, the difference in the ratio of Ca(OH)2 to nano-SiO2 does not cause a strong change in the XRD pattern, while the Al in the system 3+ It also has little effect on the composition of the product; a small amount of residual Ca(OH)2 was found in the CSH-1.5 sample, and a small amount of Kato stone was also observed to be formed in CASH-1.5. It can be seen that under high Ca / Si conditions, other products or residual raw materials that have not been reacted will inevitably appear in the system. Therefore, when selecting the raw materials for supplementing gelation, the molar ratio of Ca(OH)2 to nano SiO2 should be avoided as much as possible.

[0109] And, as Figure 2As shown in (a), the intensity of the d(110) diffraction peak (FWHM) at 2θ = 29.22° varies among different samples. FWHM specifically refers to the d(110) diffraction peak at 2θ = 29.22° for different samples. d(110) represents the (110) crystal plane of CSH or CASH crystals. By comparing the crystallinity of the products generated in different sets of examples, it was found that the intensity of this diffraction peak is closely related to the crystallinity of CSH or CASH. That is, the smaller the intensity of FWHM, the higher the crystallinity, and the larger the intensity of FWHM, the lower the crystallinity. Figure 2 As shown in (b), the FWHM intensity corresponding to the CASH group is generally greater than that corresponding to the CSH group. The reason for this result is that Al 3+ Replacement of Si 4+ Entering the interlayer structure, it leads to an increase in the interlayer spacing of the crystal, which in turn leads to a significant increase in the strength of FWHM; and the FWHM strength corresponding to both the CSH group and the CASH group increases with the increase of the molar ratio of Ca(OH)2 to nano SiO2, that is, the higher the molar ratio of Ca(OH)2 to nano SiO2 in the raw materials, the lower the crystallinity of the product.

[0110] It is important to emphasize that although the preparation process has removed carbonate ions from the raw materials as much as possible through boiling deionized water and sealing, a small amount of carbonate ions are still inevitably retained in the deionized water. Therefore, the samples produced in each set of examples contain a small amount of calcium carbonate, but the observed calcium carbonate content is very low, so the effect on the pH of the product is also very small, and it does not affect the generation and characteristics of CSH or CASH in each set of examples.

[0111] X-ray diffraction experiments were conducted on samples from Examples ③, ④, and ⑦ to ⑩ to investigate the effect of different curing times on the composition of the cement supplementary gel phase, and the results were as follows: Figure 3 (a) shows the XRD pattern; by detecting the diffraction signal generated by X-rays passing through the crystal, information such as the phase composition, crystal structure, grain size, and stress state of the material is analyzed; the analysis shows that the curing time has little effect on the phase composition of CSH or CASH, but... Figure 3 As shown in (b), the FWHM strength of both CSH and CASH decreased with the extension of curing time, indicating that the extension of curing time is conducive to the formation of structurally ordered CSH or CASH.

[0112] For Examples ③, ④, The generated samples were subjected to X-ray diffraction experiments to investigate the effect of different curing temperatures on the composition of the cement supplementary gel phase, and the results were as follows: Figure 4 (a) shows the XRD pattern; analysis shows that curing temperature has little effect on the phase composition of CSH or CASH, and... Figure 4 In (a), two example samples of CSH and CASH were cured at 25°C (i.e., example samples). and Examples A d(002) diffraction peak was observed in the sample. d(002) represents the (002) crystal plane of the CSH or CASH crystal. The d(002) diffraction peak serves as an indicator of the degree of order in the cement supplement gel crystal. The greater the intensity of the d(002) diffraction peak, the greater the degree of order in the crystal. Figure 4 (a) It can be seen that, whether it is CSH or CASH, the intensity of the d(002) diffraction peak is relatively large when the curing temperature is 25℃. When the curing temperature is increased to 60℃, the d(002) diffraction peak becomes flat and almost disappears. When the temperature is increased to 95℃, d(002) disappears completely. This indicates that the sample synthesized at low temperature (25℃) has a better layered structure.

[0113] like Figure 4 As shown in (b), the FWHM intensity of the diffraction peak at 2θ = 29.22° for both CSH and CASH first increases and then decreases with increasing curing temperature. Furthermore, the FWHM intensity of CSH is lower than that of CASH under the same conditions in most cases. This result is due to the influence of Al... 3+ Replacement of Si 4+ It enters the interlayer structure, thereby increasing the interlayer spacing, which in turn leads to a significant increase in the strength of FWHM.

[0114] Thermogravimetric analysis was used to analyze the thermal stability of the supplementary gel in each embodiment.

[0115] Thermogravimetric analysis was performed on the samples generated in Examples ① to ⑥ to investigate the effect of different molar ratios of Ca(OH)₂ and nano-SiO₂ on the supplementary gelation thermal stability (TG), and the results were as follows. Figure 5 The TG test result spectrum shown and as follows Figure 6The TG-DSC curves shown indicate that all samples from Examples ① to ⑥ experienced significant weight loss in two temperature ranges: 40-350℃ and 600-750℃. Since both CSH and CASH contain adsorbed water and structural water, the weight loss in the 40-350℃ range was primarily due to the decomposition and loss of adsorbed and structural water in CSH and CASH. However, because calcium carbonate is easily decomposed at high temperatures, the weight loss in the 600-750℃ range was mainly due to the thermal decomposition of calcium carbonate in the CSH and CASH phases. Furthermore, based on… Figure 5 It can be concluded that when the molar ratio of Ca(OH)2 to nano-SiO2 is 0.5, the weight loss of CSH and CASH is significantly less than that of examples with other molar ratios, and the weight loss of CASH is slightly less than that of CSH. The reason for this result is that Al... 3+ It will combine with water molecules to form a stable [Al(H2O)6] 3+ , and Si 4+ However, it is almost impossible for Al to bind with water molecules; and in previous phase composition analysis experiments, it was found that Al... 3+ Replacement of Si 4+ Entering the interlayer structure leads to an increase in the interlayer spacing of the crystal, and this increase in interlayer spacing also leads to an increase in the interlayer water content, regardless of [Al(H2O)6]. 3+ Interlayer water is extremely difficult to decompose and lose, and the decrease in the molar ratio of Ca(OH)2 to nano-SiO2 and Al 3+ Both can lead to the growth of silicate chains, therefore it can be concluded that the increase in average silicate chain length (MCL) is beneficial to the thermal stability of CSH or CASH.

[0116] In addition, according to Figure 5 It can also be concluded that when the molar ratio of Ca(OH)2 to nano-SiO2 is 1.5, the weight loss of CASH is slightly greater than that of CSH. This is not because the above conclusion is wrong. The reason is that in the phase composition analysis experiment, a small amount of residual Ca(OH)2 was found in the CSH-1.5 sample. A small amount of Kato stone was generated in CASH-1.5. The thermal stability of Kato stone is significantly lower than that of Ca(OH)2. Therefore, the final weight loss of CASH-1.5 is greater than that of CSH-1.5.

[0117] Thermogravimetric analysis was performed on samples from Examples ③, ④, and ⑦ to ⑩ to investigate the effect of different curing times on the thermal stability (TG) of the supplemented gel, and the results were as follows: Figure 7 The TG test result spectrum shown and as follows Figure 8The TG-DSC curves shown indicate that, through analysis, the mass loss of CSH and CASH gradually decreases with increasing curing time. At any given curing time, the mass loss of CASH is less than that of CSH, and the abrupt change in the CSH exothermic peak is larger. This result is due to: Al 3+ Replacement of Si 4+ After entering the interlayer structure, Al 3+ Interlayer insertion causes structural changes.

[0118] For Examples ③, ④, Thermogravimetric analysis (TGA) was performed on the generated samples to investigate the effect of different curing temperatures on the thermal stability (TG) of the supplementary gel, and the results were as follows: Figure 9 The TG test result spectrum shown and as follows Figure 10 The TG-DSC curve shown indicates that, through analysis, the sample mass loss gradually decreases with increasing curing temperature, but the calcium carbonate content increases with increasing curing temperature, leading to... (Ca in the sample) 2+ and Si 4+ The average molar ratio is slightly lower than the target value, therefore it is necessary to adjust the value by fitting a regression equation. The measured values ​​were corrected, and a regression equation was fitted. This indicates that as the calcium content in the initial mixture increases, the measured (C / S) ratio increases. - It tends to a limit value; and according to Figure 10 The curves shown indicate that the higher the curing temperature, the better the thermal stability of CSH and CASH (the higher the maximum value of the exothermic peak).

[0119] The experimental data related to thermogravimetric analysis in the above process are shown in Table 2;

[0120]

[0121] Table 2. Mass loss (%) of C-(A)-SH at different temperature ranges

[0122] The bonding state of the supplementary gel in each embodiment was analyzed by Fourier transform infrared spectroscopy (FT-IR) experiments.

[0123] Fourier transform infrared spectroscopy (FT-IR) experiments were performed on the samples generated in Examples ① to ⑥ to investigate the effect of different molar ratios of Ca(OH)₂ and nano-SiO₂ on the cement-supplemented gel bonding state, and the results were as follows. Figure 11The FT-IR spectra shown; by identifying vibrational peaks at specific wavenumbers in the FT-IR spectra, chemical bonds such as CO bonds in carbonate structures, OH bonds in water molecules, and Si-O and Al-O bonds in aluminosilicates can be identified; analysis shows that the spectral band differences among all sample examples are small and almost identical; Figure 11 In the middle, the wavenumber is at 452cm -1 The vibration peak corresponds to the bending vibration of O-Si-O / O-Al-O, with a wavenumber of 874 cm⁻¹. -1 The sharp characteristic peaks are attributed to the asymmetric stretching vibrations of the CO bonds in a typical carbonate structure, with wavenumbers ranging from 1418 to 1474 cm⁻¹. -1 The characteristic peaks in this range are due to the symmetric stretching vibrations of the CO bonds, and the vibrational peak intensities of CASH are all lower than those of CSH, with wavenumbers around 3440 cm⁻¹. -1 and 1632cm -1 The vibrational peaks correspond to the stretching and bending vibrations of the OH bonds in water molecules, respectively; and the bandwidth of CASH is significantly higher than that of CSH, and the bandwidth of CASH also increases with the increase of the molar ratio of Ca(OH)2 to nano-SiO2. The reason for this phenomenon is that Al 3+ Replacement of Si 4+ Subsequently, the crystallinity of CSH decreased, which is consistent with the results of previous X-ray diffraction experiments.

[0124] Fourier transform infrared spectroscopy (FT-IR) experiments were conducted on samples from Examples ③, ④, and ⑦ to ⑩ to investigate the effect of different curing times on the cement's supplementary gel bonding state, and the results were as follows: Figure 12 The FT-IR spectra shown indicate that the curing time has little effect on the bonding between CSH and CASH. However, at the Si-O-Si bond bending vibration at wavenumber 660 cm⁻¹, it is clear that no Si-O-Si bond bending vibration occurs in CASH at any curing time. This phenomenon is because, in the CASH crystal, Al… 3+ Replacement of Si 4+ This results in some Si-O-Si bonds being replaced by Si-O-Al bonds, and because Al 3+ The atomic radius is greater than that of Si 4+ The atomic radius of the Al-O crystal is much smaller than that of the Si-O crystal, resulting in a longer Al-O bond length. Therefore, it is necessary to introduce bond angles with a wider angular distribution range to improve the resistance of CASH crystals to change.

[0125] For Examples ③, ④, The generated samples were subjected to Fourier transform infrared spectroscopy (FT-IR) experiments to investigate the effect of different curing temperatures on the cement's supplementary gel bonding state, and the results were as follows: Figure 13 The FT-IR spectra shown are analyzed. Analysis revealed that, except for the CASH sample cured at 95℃ in Example ④, all other samples exhibited Si-O-Si bond bending vibrations at a wavenumber of 660 cm⁻¹. The only difference in the preparation conditions of the CASH samples from different examples was the curing temperature. Therefore, it is easy to conclude that the higher the temperature, the stronger the Al... 3+ The more moles of Al enter the CSH structure, the more Al will be affected. 3+ Capable of replacing more molar amounts of Si 4+ This leads to the formation of more Si-O-Al bonds, thereby increasing the resistance of CASH crystals to change.

[0126] The microstructure and particle size of the supplementary gels in each embodiment were analyzed by scanning electron microscopy.

[0127] Electron microscopy (SEM) experiments were performed on the samples generated in Examples ① to ⑥ to investigate the effect of different molar ratios of Ca(OH)₂ and nano-SiO₂ on the microstructure of cement supplementary gel, and the results were as follows. Figure 14 The SEM images shown indicate that the calcium silicate hydrate (cement supplement gel) crystals become more compact (dense) with increasing molar ratio of Ca(OH)₂ to nano-SiO₂. Taking the CSH group as an example, this conclusion is analyzed further. Figure 14 In (a), the microstructure of calcium silicate hydrate crystals at CSH-0.5 is a flocculent network of aggregated particles with numerous pores and a large number of fine fibrous segments around each particle, and the particles are relatively dispersed. Figure 14 In (c), the microstructure of calcium silicate hydrate crystals at CSH-1.0 is still a flocculent network of aggregated particles, but the particle size is significantly larger than that in the CSH-0.5 state, and almost no fine fibrous segments can be observed around each particle; Figure 14 In (e), the microstructure of hydrated calcium silicate crystals at CSH-1.5 is still a flocculent network of aggregated particles, with particle size between CSH-0.5 and CSH-1.0. However, the compactness between the particles is significantly improved. Therefore, it can be inferred that hydrated calcium silicate crystals become more compact with the increase of the molar ratio of Ca(OH)2 to nano-SiO2. According to... Figure 14 The SEM images shown in (b, d, f) show that in the CASH group, the microstructure and particle size variations of CASH are similar to those of the CSH group, but the density of CASH is significantly higher than that of CSH. Therefore, it can be determined that Al3+ The addition of [a substance] can increase the density of CSH crystals.

[0128] Electron microscopy (SEM) experiments were performed on samples from Examples ③, ④, and ⑦ to ⑩ to investigate the effect of different curing times on the microstructure of cement-replenished gel, and the results were as follows. Figure 15 The SEM images shown reveal that hydrated calcium silicate crystals become denser and larger with increasing curing time. However, the mesh clarity of the CASH group is significantly higher than that of the CSH group. This phenomenon is attributed to the fact that longer curing times result in higher Al content. 3+ The more molar amount of CSH crystals infiltrated, the higher the density of the CSH crystals, which in turn makes the network morphology on the surface of the CSH crystal particles more obvious.

[0129] For Examples ③, ④, The generated samples were subjected to scanning electron microscopy (SEM) experiments to investigate the effect of different curing times on the microstructure of cement-replenished gel, and the results were as follows: Figure 16 The SEM images shown reveal that, in the CSH group, the density of hydrated calcium silicate crystals initially increases and then decreases sharply with increasing curing temperature, while the crystal size increases. Combined with the thermogravimetric analysis results, which indicate that the calcium carbonate content increases with increasing curing temperature, the reason for the decrease in density of CSH crystals under high-temperature curing conditions is that both the synthesis rate of CSH crystals and the formation rate of calcium carbonate increase with increasing temperature. In this curing container, the synthesis rate of CSH crystals increases, thus requiring more calcium carbonate. 2+ The formation of calcium carbonate will compete with the calcium in the curing container. 2+ This leads to the presence of Ca in the CSH crystal. 2+ Insufficient content leads to a decrease in the density of CSH crystals under high-temperature curing conditions; in the CASH group, the density of hydrated calcium silicate crystals increases with increasing curing temperature, and the grain size also increases accordingly. Combined with the conclusions of Fourier transform infrared spectroscopy experiments, Al... 3+ Replacement of Si 4+ Afterwards, it can improve the resistance to change of CASH crystals, therefore for Ca 2+ The effect is stronger, and it can prevent the formation of calcium carbonate from affecting Ca. 2+ Competition.

[0130] Therefore, increasing the molar ratio of Ca(OH)2 to nano-SiO2, reducing the curing time, and lowering the curing temperature can yield CSH or CASH crystals with smaller grain sizes. However, the volume of CSH or CASH crystals is already at the micrometer level. A high molar ratio of Ca(OH)2 to nano-SiO2 can lead to the formation of a second type of crystal. A short curing time can reduce the order and density of the crystals. A low curing temperature can reduce the thermal stability and resistance to deformation of the crystals, which in turn can reduce the performance of cement supplementary gel.

[0131] In summary, the preparation conditions and proportions of the cement supplement gel described in Example ④ are optimal. It has excellent thermal stability, does not produce a second product during the preparation process, has high structural order, high thermal stability, extremely high resistance to deformation and density, and relatively moderate grain size.

[0132] Therefore, this scheme selects CASH-1.0_95℃_7d prepared in Example ④ as a supplementary gel to be added to cement, and explores the effects of different dosages of cement supplementary gel on the workability, hydration heat release, pore structure and mechanical strength of cement-based materials.

[0133] The optimal cement supplement gel (CASH) was prepared according to the preparation process described in Example 4. The prepared CASH was placed in water and vibrated with an ultrasonic vibrator for at least 30 minutes to disperse it in the aqueous solution. Then, the aqueous solution containing dispersed CASH was used to prepare cement. The final prepared cement met the following requirements: cement mortar water-cement ratio of 0.52, mortar-cement ratio of 1:3, and cement paste water-cement ratio of 0.32. Finally, mortar test blocks were cured under the same standard curing environment for 1, 3, 7, and 28 days, respectively, with CASH dosages of 0 wt%, 1 wt%, 3 wt%, and 5 wt%, respectively.

[0134] During the investigation, since the main performance characteristics of cement-based materials are fluidity and setting time, this plan only focuses on experiments related to fluidity and setting time. Figure 17 and 18As shown, the fluidity of cement paste with 0 wt% CASH was 185 mm; the fluidity of cement paste with 1 wt% CASH was 166 mm; the fluidity of cement paste with 3 wt% CASH was 147 mm; and the fluidity of cement paste with 5 wt% CASH was 135 mm. Compared with cement paste with 0 wt% CASH, cement paste with 1 wt% CASH had a 15.6% reduction in initial setting time and a 19.8% reduction in final setting time; cement paste with 3 wt% CASH had a 23.6% reduction in initial setting time and a 33.1% reduction in final setting time; and cement paste with 5 wt% CASH had a fluidity of 135 mm. The initial setting time of SH cement paste was reduced by 32.2%, and the final setting time was reduced by 41.8%. Therefore, it can be concluded that, under reasonable dosage, CASH can significantly reduce the fluidity and setting time of cement paste, and the greater the dosage, the greater the reduction in fluidity and setting time. However, reasonable dosage is a prerequisite. Since the requirements for cement vary in different buildings, this study only explores the effect of CASH on the workability of cementitious substrates and does not provide specific dosages. The specific amount of CASH to be added is easily obtained by those skilled in the art and will not be elaborated here.

[0135] like Figure 19 As shown in Table 3, the higher the amount of cement supplement gel, the less time it takes to reach the maximum heat release rate during cement hydration. However, the maximum heat release rate during hydration first increases and then decreases. In particular, the total heat release of the experimental group with a cement supplement gel content of 5 wt% after long-term hydration is slightly lower than that of the experimental group with a content of 3 wt%.

[0136]

[0137] Table 3 Detailed parameters of the cement hydration process

[0138] Hardened cement paste has a highly complex structure, characterized by discontinuous and non-uniform composition and porosity. The porosity, pore size distribution, and pore geometry of these pores directly affect the strength, durability, and permeability of cement-based materials. Therefore, it is also necessary to analyze the influence of cement-added gel on the pore structure after cement hardening. Figure 20 and 21 As shown, the pore size decreases with increasing cementitious gel content and also with increasing curing time of the mortar specimen.

[0139] like Figure 22As shown, although the compressive strength of cement increases with the increase of curing time, the cement with the highest compressive strength is found in the experimental group with a cement supplement gel dosage of 5wt% when the curing time is 1 day, the cement with the highest compressive strength is found in the experimental group with a cement supplement gel dosage of 3wt% when the curing time is 3 days, and the cement with the highest compressive strength is found in the experimental group with a cement supplement gel dosage of 1wt% when the curing time is greater than 7 days.

[0140] The above are the preferred embodiments described in this invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of this invention, and these improvements and modifications should also be considered within the scope of protection of this invention.

Claims

1. A method for characterizing and analyzing supplementary gels, characterized in that: Includes the following steps: Step A: Simultaneously prepare multiple sets of cement supplement gels prepared under different conditions; Step B: Based on variables such as different molar ratios of raw materials, different curing times, and different curing temperatures, the prepared multiple groups of different cement supplementary gels were divided into three control test groups; Step C: Perform X-ray diffraction experiments on each control experimental group in sequence to analyze the phase composition of the cement supplement gel generated under different preparation conditions; Step D: Perform thermogravimetric analysis on each control experimental group sequentially to analyze the thermal stability of the cement supplement gel generated under different preparation conditions. Step E: Perform Fourier transform infrared spectroscopy experiments on each control experimental group in sequence to analyze the bonding state of the cement supplement gel generated under different preparation conditions; Step F: Perform electron microscopy scanning experiments on each control experimental group in sequence to analyze the microstructure and particle size of the cement supplement gel generated under different preparation conditions; Step G: Analyze the experimental results of steps C to F and select the optimal preparation conditions for cement supplement gel.

2. The method for preparing a supplementary gelling agent according to claim 1, characterized in that: Step A includes the following steps: Step 1: Boil the deionized water and then cool it to 25°C to remove dissolved CO2, then transfer it to a polytetrafluoroethylene container; Step 2: Add Ca(OH)2 to the deionized water from Step 1 and ultrasonically disperse it at a frequency of 20 kHz for at least 3 minutes; Step 3: Based on Step 2, add nano-SiO2 to the deionized water and ultrasonically disperse it at a frequency of 20KHz for at least 3 minutes; Step 4: Based on Step 3, add nano-Al2O3 to the deionized water and ultrasonically disperse it at a frequency of 20KHz for at least 3 minutes; Step 5: Based on Step 4, seal the PTFE container and magnetically stir it at 95°C for 1.5 hours; Step Six: After completing Step Five, transfer the sealed PTFE container to a water bath for curing. Step 7: After completing Step 6, filter the polytetrafluoroethylene container synthesis product and transfer the filtered product to a washing device. Step 8: Wash the synthesized product filtered in Step 6 with deionized water at least twice; Step Nine: After completing Step Eight, wash the synthesized product filtered in Step Six with anhydrous ethanol at least twice. Step 10: Place the synthetic product washed in Step 9 into a freeze dryer and dry it to constant weight to obtain C-(A)-SH.

3. The one according to claim 2, characterized in that: In steps one to four, the molar ratio of the raw materials satisfies: Ca / Si = 0.5 to 1.5; Al / Si = 0 or 0.1, and the mass ratio of deionized water to the total mass of the raw materials is 8.0:

1.

4. The one according to claim 2, characterized in that: If Al / Si = 0, the synthetic product obtained in step six is ​​a cement supplement gel of the CSH phase; if Al / Si = 0.1, the synthetic product obtained in step six is ​​a cement supplement gel of the CASH phase.

5. The one according to claim 2, characterized in that: In step five, the water bath curing environment is a sealed container to prevent CO2 from entering.

6. The one according to claim 2, characterized in that: In step six, the water bath temperature is 25℃~95℃, and the curing time is 1~7 days.

7. An analytical method for the effect of supplementary cementitious gel prepared according to claim 1 on cement, characterized in that: Includes the following steps: Step S1: Prepare several identical portions of cement paste; Step S2: Prepare several cement supplement gels according to the preparation method of cement supplement gel selected in step G; Step S3: Add the cement supplement gel prepared in step S2 to the cement paste prepared in step S1 according to different dosages; Step S4: Group the cement slurry with the same cement supplement gel into one group, and each part of cement slurry in each group is cured for a different duration. Step S5: In step S4, the cement paste of each component is tested, and the effects of different dosages of cement supplementary gel on the workability, hydration heat release, pore structure and mechanical strength of cement-based materials at different curing times are analyzed.